5c-9=3c+1

Simple and best practice solution for 5c-9=3c+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5c-9=3c+1 equation:


Simplifying
5c + -9 = 3c + 1

Reorder the terms:
-9 + 5c = 3c + 1

Reorder the terms:
-9 + 5c = 1 + 3c

Solving
-9 + 5c = 1 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
-9 + 5c + -3c = 1 + 3c + -3c

Combine like terms: 5c + -3c = 2c
-9 + 2c = 1 + 3c + -3c

Combine like terms: 3c + -3c = 0
-9 + 2c = 1 + 0
-9 + 2c = 1

Add '9' to each side of the equation.
-9 + 9 + 2c = 1 + 9

Combine like terms: -9 + 9 = 0
0 + 2c = 1 + 9
2c = 1 + 9

Combine like terms: 1 + 9 = 10
2c = 10

Divide each side by '2'.
c = 5

Simplifying
c = 5

See similar equations:

| 36x+21-3x=3x-21 | | 2-6y=11-x | | 3v^2+5v-18=0 | | 3.6+0.3x=0.9 | | (1,5);m=-2/3 | | 11+5x=13-x | | 21y-3+24y+42= | | 6x+7.22=4x+10 | | 2t+25=8t-7 | | 6.2x-1.6=23.2 | | 7(a)+4.50(k)=64-4a | | 0.6x+19.1=x-1.82 | | 225a^2-36b^2=0 | | 4.04m+4.04m= | | 9=3x+17 | | 7.7x-2.3=13.1 | | (p+12)=(p-15) | | -2x^2+2x=-5 | | o=x^2-15x | | 0.4x+11.1=x-9.42 | | 6-7a+1=7+a | | 3log(2x-2)=x-2 | | 3(3x-2.8)=2x-8.4 | | 7a-31=74 | | 2n/3-3/7 | | 8g+6t+5t-1t-6g= | | p+12=p-15 | | 7/8:x::4/5:2/3 | | .08-.01(x+1)=-.02(4-x) | | 4+8+5z-3z+6= | | -6x-1(3x+4)= | | 5x-10x=10x+5 |

Equations solver categories